Article retraction rates in selected MeSH term categories in PubMed published between 2010 and 2020 - Alexander, Robert; Peterson, Christopher J; Yang, Shengping; Nugent, Kenneth (Accountability in research, 2025)
* Article retractions occurred in all subsets of articles classified by the 15 PubMed MeSH terms used in this study. * The time to retraction and the rate of retraction differed significantly across research topics classified by these MeSH terms. This suggests that research content and visibility affect retraction rates. * As an example, the "Neoplasms" category had the highest total number of retractions (993) and one of the highest retraction rates (75.4 per 100,000 publications). * Readers, editors, and authors need to understand that retractions do occur following publication in the medical literature. These retractions potentially have important consequences and require attention from all individuals involved in the multiple steps needed to create high-quality medical and scientific information. Academic article retractions occur across all disciplines, though few studies have examined the association between research topics and retraction rates. We assessed and compared the rate of retraction across several important clinical research topics. Information about the number of publications, the number of retractions, the retraction rate, and the time to retraction was collected for articles identified by 15 Medical Subject Headings (MeSH) terms. These articles were published between 1 January 2010 and 31 December 2020. The searches took place between 18 September 2021 and 24 October 2021. The MeSH terms were selected based on our clinical experience with the expectation that there will be multiple publications during the timeframe to use for the searches. Additional topics were selected based on the frequency of controversy in the public media and were identified by the Altmetric Top 100 report. The mean number of publications for all categories was 181,975 ± 332,245; the median number of publications was 67,991 [Q1, Q3; 31951.5, 138,981.5]. The mean number of retractions was 100.3 ± 251.3, and the median number of retractions was 22 [Q1, Q3; 6.5, 53]. The mean time to retraction ranged from 114 days to 1,409.5 days; the median was 857.3 days [Q1, Q3; 684.7, 1098.6], depending on the topic. The various MeSH term categories used in this study had significant differences in retraction rate and time to retraction. The "Neoplasms" category had the highest total number of retractions (993) and one of the highest retraction rates (75.4 per 100,000 publications). All PubMed categories analyzed in this study had retracted articles. The median time to retraction was 857 days. The long delays in some categories could contribute to potentially misleading information which might have adverse effects on clinical decisions in patient care and on research design. Rate of retraction varies across research topics and further studies are needed to explore this relationship.